2023
DOI: 10.1039/d3ce00086a
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of a base component to porous organic salts and their CO2 storage capability

Abstract: Porous organic salts (POSs) are constructed by charge-assisted hydrogen bonding between amino and sulfonic groups, and can design a variety of porous structures based on the molecular design. In particular,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…[110] The efficient and robust supramolecular structure of [4 + 4] ion-pair clusters consisting of four ion pairs can be used as materials for gas adsorption and sensing. [111][112][113][114][115][116] Organic amidines are more basic than amines and have similar directionality to carboxylic acids. Supramolecular structures based on organic carboxylic acids and amidines are constructed by White.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[110] The efficient and robust supramolecular structure of [4 + 4] ion-pair clusters consisting of four ion pairs can be used as materials for gas adsorption and sensing. [111][112][113][114][115][116] Organic amidines are more basic than amines and have similar directionality to carboxylic acids. Supramolecular structures based on organic carboxylic acids and amidines are constructed by White.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Tohnai reported that Porous organic salts (POSs) were prepared by organosulfonic acid and triphenylmethylamine [110] . The efficient and robust supramolecular structure of [4+4] ion‐pair clusters consisting of four ion pairs can be used as materials for gas adsorption and sensing [111–116] . Organic amidines are more basic than amines and have similar directionality to carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%